2015
DOI: 10.1650/condor-14-131.1
|View full text |Cite
|
Sign up to set email alerts
|

Distance sampling survey and abundance estimation of the critically endangered Grenada Dove (Leptotila wellsi)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The upper values reflect the assumption that the sex ratio in the population is equal (Bibby et al 2000), but in highly threatened populations females are often much less numerous (Donald 2007), so the dove’s actual population size may be even lower than the 100 and 136 speculated. More recently, however, a distance sampling survey has produced a population estimate of 160 (± 30) based on 33 doves either heard or observed (Rivera-Milán et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The upper values reflect the assumption that the sex ratio in the population is equal (Bibby et al 2000), but in highly threatened populations females are often much less numerous (Donald 2007), so the dove’s actual population size may be even lower than the 100 and 136 speculated. More recently, however, a distance sampling survey has produced a population estimate of 160 (± 30) based on 33 doves either heard or observed (Rivera-Milán et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The habitat preference findings of this study are preliminary, and could be improved by a greater quadrat size for habitat measurement and more accurate linkage of point count results to habitat plots; while 60 m association distance has been used in other studies on similar species (Rivera-Milán et al 2015), it adds uncertainty to the results. However, as little is known about this highly threatened species, the findings still have potential importance in directing conservation action.…”
Section: Discussionmentioning
confidence: 92%
“…GPS co-ordinates of all Negros Bleeding-heart sightings from both expeditions were mapped using ArcMap v.10.4 (ESRI 2016) along with the co-ordinates of habitat measurement points. The Negros Bleeding-heart was marked as associated to any habitat data-points within 60 m of a sighting’s co-ordinates, following protocol for the ground-forager dove Leptotila wellsi (Rivera-Milán et al 2015). Four camera traps (Bushnell 12 MP Trophy Low Glow Essential HD Trail Camera) were placed at knee height above the ground from 21 June 2018 – 14 July 2018, and four more were added from 17 July until 6 June 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no studies have quantified the influence of point-level vegetation on Honduran Emerald abundance. Several studies in avian ecology have previously demonstrated the utility of habitat-species abundance relationships to highlight the role of vegetation structure and composition for species conservation (Pardini et al 2005, Gómez-Montes andBayly 2010) and to assess the population status of species in a given locality (Sillett et al 2012, Rivera-Milán et al 2015. Therefore, blueprints exist to study how Honduran Emerald local abundance is driven by vegetation characteristics in tropical dry forest remnants.…”
Section: Introductionmentioning
confidence: 99%